PP.23.25: ROLE OF 3 DIMENSIONAL RECONSTRUCTION IN RIGHT ADRENAL VENOUS SAMPLING. (June 2015) - Hui, C.; Wang, H.; Zhang, Z.
Abstract : Objective: Adrenal venous sampling(AVS) is recommended as the gold standard procedure for subtype classification in PA, but the procedure is challenging and the right adrenal vein (RAV) particularly difficult to cannulate because it is short, variable and enters the inferior vena cava (IVC) at an acute angle. Our purpose was to find a feasible method in right adrenal venous cannulation by using MDCT with three dimensional reconstruction before AVS. Design and method: From August 2013 to April 2014, a total of 20 patients with confirmed PA who had a unilateral or bilateral adrenal morphology abnormalities (including Hyperplasia or adenoma which diameter <1 cm) underwent AVS were analyzed retrospectively.7 of the patients used MDCT with 3 dimensional before AVS, the other 13 patients without using MDCT with 3 dimensional before AVS served as controls. To compare the rate of correct cannulation, contrast volume used, and time of right adrenal venous sampling between two groups above. Successful adrenal vein catheterization is defined by a ratio of >3:1 of cortisol in the adrenal vein vs the inferior vena cava. Results: As compared to controls, using MDCT with three dimensional reconstruction before AVS increased the rate of correct cannulation into RAV from 23.1% to 85.7% (p < 0.05), decreased the contrast volume about 1/3 (23 ± 4 vs60 ± 18, p < 0.05) and shortened the time to identify RAV by 50%(14.2 ± 3.1 vs 29.7 ± 6.8, p < 0.05). By contrast MDCT with three dimensional reconstruction and angiography, 7 patients catheter misplacement lead to failure of right adrenal venous sampling before using MDCT. Conclusions: MDCT with three dimensional reconstruction used before AVS might provide visual confirmation of correct cannulation, decrease the contrast volume, shorten the time to identify RAV, and improve success rates of RAV sampling.